2000
DOI: 10.1159/000013626
|View full text |Cite
|
Sign up to set email alerts
|

Membranous Glomerulonephritis with Nephrotic Syndrome Associated with Chronic Lymphocytic Leukemia

Abstract: A 66-year-old woman was admitted to our hospital for evaluation of edema of the extremities. Laboratory findings suggested that she had nephrotic syndrome and chronic lymphocytic leukemia (CLL). Renal biopsy (with PAM staining) showed a spike formation in the capillary wall. Immunofluorescent staining revealed deposition of immunoglobulin G (IgG) and the third component of complement in the glomerular basement membrane. Electron microscopy showed fibrillary deposits in the subepithelium. These findings indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Furthermore, 4/8 MGN cases had lymphocytic infiltration, which was restricted to the interstitial region and not directly associated with the occurrence of nephrotic syndrome [4]. In the present case, the infiltrative lymphocytes were morphologically and phenotypically the same as CLL cell.…”
Section: Case Reportsupporting
confidence: 43%
See 2 more Smart Citations
“…Furthermore, 4/8 MGN cases had lymphocytic infiltration, which was restricted to the interstitial region and not directly associated with the occurrence of nephrotic syndrome [4]. In the present case, the infiltrative lymphocytes were morphologically and phenotypically the same as CLL cell.…”
Section: Case Reportsupporting
confidence: 43%
“…The pathophysiology of glomerulonephritis in CLL is considered to be related to the glomerular deposition of the monoclonal component secreted by the B-cell clone or to the formation of immune complexes [2,3]. Eight MGN cases with nephrotic syndrome in CLL have been reported to date [4]. We now present another case and review the previously reported from the viewpoint of histological and immunological data.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most of these CLL-associated cases are single patient case reports or small case series, with the largest report to date including 15 patients. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Here we report the pathological findings and outcomes of a series of 49 patients with CLL and MBL followed at a single institution, who underwent a kidney biopsy during the course of their disease to evaluate renal insufficiency and/or nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…qPCR performed on plasma samples showed steadily increasing levels of BK virus DNA over time, which coincided with decreasing renal function. We excluded a number of explanations other than BKVN as the cause of his nephropathy, including CLL invasion in the kidneys, CLL-associated glomerular lesions such as membranous or membrano-proliferative glomerulopathy, 11 GvH disease, and relevant viral infections.…”
Section: Discussionmentioning
confidence: 99%